The sign painter : a novel - Bunn, T. Davis, 1952- (Howard Books, a division of Simon & Schuster, Inc., 2014)
"Amy Dowell had always considered herself a very good mother. But when she loses her husband to illness and her home to debt, she finds herself and her young daughter Kimberly living on the streets as she struggles to find a job that will get them back on their feet again. When Amy meets Lucy Watts, the pastor in charge of the church program that fed Amy and Kimberly their latest meal, Lucy sets them up in temporary housing and gives her a lead on a job painting signs for a local auto dealership--but Amy is hesitant to let go and trust"--Amazon.com.